Blogi fan fiction jako nowy element współczesnej kultury (rekonesans badawczy) = Fanfiction blogs as a new element of present culture - Półtorak, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is a supplement to a broader discussion about the functioning of the literary Internet users in the new medium. It is also a continuation of the author?s study on the importance of literature in Internet communications. Today, the Internet is not only a source of information, but also the space of social activity in all areas, including culture.
Keywords: komunikacja; internet; kultura popularna; blog; nadawca; odbiorca; fan fiction; communication; pop culture; sender; recipient